MOTIVATIONS FOR CAREER TRANSITIONS: A COMPARATIVE STUDYOF MILITARY PERSONNEL TRANSITIONING INTO THE FIELD OFEDUCATION - Kalmanovich, Adva (E-Journal VFU, 2024)
This study investigates the transition of Israeli military veterans to school leaders. Interviews and surveys were conducted on 40 retired career military personnel who chose to pursue a new career as school principals and leaders. The study also includes feedback from the teaching staff regarding the intergration of career veterans into the education system. Findings show that the approach taken by the veterans as eduction leaders was directly tied to specific identity anchors. Their focus was either on their military training, on education, or on their individual desires to excel and use their experience as school leaders as a stepping stone for future career choices.